PENGARUH TERPAAN MEDIA TERHADAP REPUTASI LEMBAGA PEMERINTAH - Tias Mustika; Rosita Anggraini (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2019)
The purpose of this study was to determine the effect of media exposure on reporting cases of alleged corruption in the sale and purchase of positions on Television on the reputation of the Ministry of Religion in Cipadu residents, Tangerang. The theory used in this research is exposure to the media and reputation. This research uses a quantitative approach by distributing questionnaires to respondents with explanatory analysis. The results of the study explained that Ha who stated that there was an influence between the variables of media exposure regarding the reporting of alleged cases of corruption in buying and selling positions on Television on the reputation of the Ministry of Religion on Cipadu Tangerang residents was received. Ho also pointed out that there was no influence of the media exposure variable on reporting cases of alleged corruption in the sale and purchase of positions on the reputation of the Ministry of Religion in Cipadu residents, Tangerang rejected. The magnitude of the level of the effect coefficient interval lies in the low region, so it can be concluded that the media exposure to the reputation of the Ministry of Religion has a low influence.